Transnational Links in Rhino Poaching and the Black Market Price of Rhino Horns - Lopes, Adrian (2019)
The trends of rhino poaching in South Africa and India – major range states – have been remarkably similar over time. Organized criminal syndicates manage an illegal supply chain of rhino horns from poachers, middlemen, and corrupt authorities, to East Asian black-markets. In this paper, we use rhino poaching data from South Africa and India to examine the plausibility of transnational links and coordination in their supplies of rhino horns. We develop an innovative model of oligopolistic collusion in supply and find empirical evidence to support the theory, while controlling for rhino horn demand features, corruption, governance quality, and conservation policy. Furthermore, we propose an inventory management model of a criminal syndicate that controls the horn supply chain. The method retraces and forecasts black-market prices, and has potential applicability in estimating supply or demand elasticities. This paper is a first to suggest an oligopolistic feature of the poaching industry. It highlights the need to reorient conservation policy to account for possible coordination of rhino horn supplies between range states.